Analysis of hotel ratings and price range in labuan bajo, Indonesia - I Wayan Pio Pratama; Ondi Asroni (Jurnal Mantik, 2023)
This research aimed to analyze the ratings and reviews of hotels in Labuan Bajo, Indonesia to understand the quality of hotels in Labuan Bajo. Data was collected from a popular online travel booking platform and pre-processed to exclude hotels with less than 10 reviews. K-means clustering was used to identify the optimum number of clusters, which was found to be 3, based on the elbow method. Cronbach alpha analysis was also performed with a value of 0.92, indicating a high level of reliability in the data. Correlation analysis was then performed on each cluster, revealing positive correlations between cleanliness, location, and facilities with overall satisfaction in cluster 0, and negative correlations between cleanliness, service, and value for money with overall satisfaction in cluster 1. The findings from this study imply that further improvement is necessary to meet the expectations of travelers in terms of service, value for money, and cleanliness in hotels located in Labuan Bajo.